Superior Knowledge, Price Discrimination, and Customer Inspection - Li, Xi; Xu, Zibin (Marketing Science, 2022)
Firms in many industries obtain superior knowledge of customer preferences through industry experience or data analytics, whereas customers often need costly efforts to learn their match values. In this paper, we examine the situations under which a customer chooses whether to inspect upon observing her personalized price from a firm with superior knowledge. On the surface, it seems that the firm can use personalized prices to directly communicate the customers’ match value, and thus there is no need for customers to expend inspection efforts. However, we find that in equilibrium the firm may trick low-preference customers into overpaying more than their match value, even when the inspection cost is low. The opportunistic incentives induce customer suspicions, which may lead to excessive customer inspection that would be avoided if the firm were not capable of price discrimination. Therefore, personalized pricing cannot obviate customer inspection. Since inspection cost raises a deadweight loss in social welfare, public policies that prevent firms from price-discriminating against customers may benefit both firms and customers. History: Yuxin Chen served as the senior editor for this article and Zsolt Katona served as associate editor for this article. Funding: This work was supported by the Hong Kong Research Grants Council [Grant 21500920] and the National Natural Science Foundation of China [Grant 72172089]. Supplemental Material: The e-companion is available at https://doi.org/10.1287/mksc.2022.1355 .